Pemberian ekstra jus putih telur terhadap kadar albumin dan Hb pada penderita hipoalbuminemia - Nurul Huda Syamsiatun; Tri Siswati (Jurnal Gizi Klinik Indonesia, 2015)
Background: Hospitals malnutrition has been reported to occur in almost 40% of patients hospitalized. Hypoalbuminemia is one of sign of malnutrition. Hypoalbuminemia can be resolved with intravenous albumin and a high albumin diet can be done by administering an extra egg white (albumin) on diet. By feeding in the form of a refreshing juice will hopefully can increase the food intake, which is expected to help improve albumin and hemoglobin (Hb) in blood level.Objective: The aim of this research is knowing the effect of egg white juice of the albumin and Hb levels in patients hipoalbumin.Method: This type of research is experimental approach with pretest-posttest control group design. While the treatment effect assessed from differences in measurement results (albumin and Hb level) between the 2 groups. The study was conducted in Sardjito and P. Senopati Bantul Hospital. The  treatment group will be given a hospital standard diet and given extra egg white juice 3x/day for 7 consecutive days. The control group was given a hospital standard diet and extra egg white as a side dish. Data were analyzed using t-test with 95% CI.Results: The mean of albumin increase in the treatment group was higher (0.5215 ± 1.6852) than the control group (0.007 ± 0.4522) (p=0.001). The mean of Hb increase in treatment group (1.685 ± 1.5898) was higher than the control group (0.929 ± 2.3169), but not statistically significant (p=0.163).Conclusion: Giving extra egg white juice 3x/day for 7 days it can be used as an alternative to high-protein diets, they are inexpensive (low cost) and easily administered to the patient, and can increase in albumin levels.